Agency support for at-risk families: service provision, challenges and effective elements for intervention - Sarah Whitcombe-Dobbs; Eve Lafferty; Charlene Rapsey; Michael Tarren-Sweeney; Annabel Ahuriri-Driscoll (Kōtuitui)
There is an urgent need to locate effective interventions for parents involved with child protection services (CPS), Oranga Tamariki in Aotearoa New Zealand. This article describes a qualitative research study that sought to understand: (1) the nature of service provision to families; (2) workers’ perceptions of challenges and effective treatment components in delivering intervention; and (3) effective practices for working with Māori. Participants were staff members working within NGOs, providing interventions to families with ongoing Oranga Tamariki involvement. Data comprised responses to semi-structured interviews (n = 9), interpreted using thematic analysis. Findings highlighted that all participants worked within family homes to deliver intervention, and drew on Te Whare Tapa Whā. Challenges included ongoing child maltreatment concerns and participants’ sense of responsibility for keeping children safe whilst being unable to do so adequately within their non-mandated roles. Perceived effective elements were: strong relationships, transparency, and having courageous conversations when needed. For indigenous clients, self-determination and the effects of colonisation were of prime importance. Themes highlighted responsive practice, with a pragmatic understanding that family priorities may not always align with professional views. This is consistent with international findings regarding challenges in delivering parenting interventions and identifies potential essential components for effective practice. HIGHLIGHTSPractitioners’ perceptions of essential elements to effective practice included: strong relationships, honesty, reciprocity, and directness regarding child protection concerns.Effective practices seen to be particular to working with Māori families were trusting, reciprocal relationships and ensuring self-determination and autonomy.Ethical tensions and a sense of complicity and helplessness at times were described, with ongoing child protection concerns evident during intervention for some families.Practitioners took a holistic approach to their work, expressing non-judgment, sympathy for, and understanding of the complex circumstantial and personal challenges faced by Oranga Tamariki-involved parents.Glossary of Māori terms: awhi: embrace, cherish; kaimahi: staff members; kanohi ki te kanohi: face to face; karakia: blessing; kaupapa Māori: Māori approach; kete: basket; kōrero: to speak; mana: prestige; manaakitanga: hospitality; mana whenua: people with rights over the land; marae: meeting house; Pākehā: New Zealander of European descent; pepeha: introduction; pēpi: baby; pono: true; pōwhiri: welcome ceremony; tamariki: children; tangata: people; tika: correct; tikanga: custom; tutū: mischevious; waiata: song; whakapapa: genealogy; whānau: family; whanaungatanga: relationship; whare: house.